Risk factors for pneumonitis in patients treated with anti‐programmed death‐1 therapy: A case‐control study - Pengfei Cui; Zhefeng Liu; Guoqiang Wang; Junxun Ma; Yuanyu Qian; Fan Zhang; Chun Han; Yaping Long; Ye Li; Xuan Zheng; Danyang Sun; Jing Zhang; et al. (Cancer Medicine)
Abstract Immune checkpoint blockade‐related pneumonitis is a rare but potentially life‐threatening adverse effect, but its risk factors are not completely understood. This case‐control study was conducted to identify pneumonitis risk factors in patients treated with anti‐PD1 monoclonal antibodies (mAbs), including all the patients who developed pneumonitis after anti‐PD‐1 mAbs treatment in the Cancer Center of the Chinese People's Liberation Army from September 2015 to September 2017. Two controls per case were matched according to a propensity‐score matching algorithm to account for confounding effects caused by individual baseline variables. Demographic and clinical information was obtained from medical records. In total, 55 cases and 110 controls were included in the study. No association was observed between smoking status or primary lung cancer and risk of pneumonitis. Significant risk factors for pneumonitis related to anti‐PD‐1 mAbs were prior thoracic radiotherapy, prior lung disease and combination therapy with odds ratios of 3.34 (1.51‐7.39), 2.86 (1.45‐5.64) and 2.73 (1.40‐5.31), respectively. The associations remained significant in the multivariable logistic regression model. The risk of pneumonitis induced by anti‐PD‐1 mAbs is associated with prior thoracic radiotherapy, prior lung disease, and combination therapy. Clinicians should monitor these features in patients receiving anti‐PD‐1 therapy to optimize clinical safety and efficacy.